2017
DOI: 10.1111/dom.13149
|View full text |Cite
|
Sign up to set email alerts
|

A European, multicentre, retrospective, non‐interventional study (EU‐TREAT) of the effectiveness of insulin degludec after switching basal insulin in a population with type 1 or type 2 diabetes

Abstract: AimsTo evaluate the clinical effectiveness of switching to insulin degludec (IDeg) in insulin‐treated patients with either type 1 diabetes (T1DM) or type 2 diabetes (T2DM) under conditions of routine clinical care.Materials and MethodsThis was a multicentre, retrospective, chart review study. In all patients, basal insulin was switched to IDeg at least 6 months before the start of data collection. Baseline was defined as the most recent recording during the 3‐month period before first prescription of IDeg. Val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
75
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(82 citation statements)
references
References 19 publications
7
75
0
Order By: Relevance
“…† P <0.05. Data for the overall population were published in the primary manuscript ; all changes were from baseline. Glargine U100, insulin glargine 100 units/ mL ; ID et, insulin detemir; n , number of participants; NPH , neutral protamine Hagedorn.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…† P <0.05. Data for the overall population were published in the primary manuscript ; all changes were from baseline. Glargine U100, insulin glargine 100 units/ mL ; ID et, insulin detemir; n , number of participants; NPH , neutral protamine Hagedorn.…”
Section: Resultsmentioning
confidence: 99%
“…Limitations of the present analysis include those of the study previously reported, such as its observational, retrospective design and the absence of a comparator arm [12]. In addition, participants in EU-TREAT were empirically (a) Type chosen, as people were switched to degludec because of difficulties while on their previous regimens, and demographic differences such as duration of diabetes and insulin treatment could potentially influence the risk of hypoglycaemia and response to the treatment change.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In an additional sensitivity analysis, long‐term costs and clinical outcomes with degludec vs glargine U100 were simulated over a 50‐year time horizon in the IQVIA CORE Diabetes Model version 9.0 (IQVIA, Basel, Switzerland) using cardiovascular risk equations from the United Kingdom Prospective Diabetes Study (UKPDS) Outcomes Model 2 and parameters detailed in Table S4 . Cost and effectiveness outcomes, the latter expressed in QALYs, were attached to each of the four scenarios detailed in Figure S2 and did not vary between treatment arms.…”
Section: Methodsmentioning
confidence: 99%